OP0048 OSKIRA-4: A Phase IIB Randomised, Placebo-Controlled Study of the Efficacy and Safety of Fostamatinib Monotherapy. (23rd January 2014) - Taylor, P. C.; Genovese, M. C.; Greenwood, M.; Ho, M.; Nasonov, E.; Oemar, B.; Stoilov, R.; Vencovsky, J.; Weinblatt, M.
Abstract : Background: Spleen tyrosine kinase (SYK) is a key enzyme in intracellular signalling of various immune cells implicated in the destruction of bone and cartilage that characterises RA. Fostamatinib (Fosta) is an oral kinase inhibitor with selectivity for SYK. Objectives: Co-primary objectives were to evaluate the efficacy of Fosta monotherapy compared with placebo on the signs and symptoms of RA over 6 weeks by DAS28-CRP and to assess non-inferiority of Fosta to adalimumab (ADA) monotherapy at week 24 by DAS28-CRP. Safety and tolerability were evaluated. (Clinicaltrials.gov : NCT01264770 ) Methods: Patients not taking current DMARDs (DMARD naïve, DMARD intolerant or with an inadequate response to <2 DMARDs) were randomised to 1 of 5 treatment arms: Fosta 100 mg bd for 24 weeks plus placebo injection every 2 weeks (PBOI) (n=54); Fosta 100 mg bd for 4 weeks, followed by 150 mg qd up to week 24, plus PBOI (n=48); Fosta 100 mg bd for 4 weeks, followed by 100 mg qd up to week 24, plus PBOI (n=57); ADA sc 40 mg every 2 weeks for 24 weeks, plus placebo to Fosta bd (n=54); placebo to Fosta bd for 6 weeks followed by switch to regimens A or B (n=52). Results: Fosta demonstrated a statistically significant improvement in DAS28-CRP score from baseline vs placebo at 6 weeks for Fosta arms A (0.56 difference [90% CI 0.21 to 0.90]) and B (0.49 difference [90% CI 0.14 to 0.84]) but not Fosta arm C (0.22 difference [90% CI -0.12 to 0.56]). Fosta 100 mg bd was superior to placebo from week 1. The Fosta arms A, B and C were significantly less effective than ADA at week 24 based on DAS28-CRP (-0.72 difference [80% CI -1.04 to -0.40]; -0.61 difference [80% CI -0.94 to -0.27]; -0.72 difference [80% CI -1.04 to -0.40] respectively). Results for secondary endpoints were generally consistent with these findings for comparisons with placebo and with ADA. Safety and tolerability findings for all Fosta arms were generally consistent with those observed in the TASKi Phase II studies. There were no deaths reported in the study. There was 1 malignancy (in the 6-week placebo period of arm E). Hypertension (13%, 6%, 9% in Fosta arms A, B and C respectively vs 9% for ADA) and diarrhoea (17%, 27%, 21% vs 2%) were the most frequent adverse events (AEs) in the Fosta groups. Serious AEs occurred in 9%, 2%, 7% vs 7%. In Fosta arms A, B and C, the most common AEs leading to discontinuations were diarrhoea (6%, 6%, 2%) and increased LFTs (6%, 2%, 5%). There were no discontinuations due to AEs in patients on ADA. Conclusions: In this Phase IIb study, Fosta demonstrated efficacy as monotherapy and met the first primary study endpoint, showing a statistically significantly superior DAS28-CRP score change from baseline compared to placebo at 6 weeks for treatment arms A and B. The study did not meet the co-primary endpoint, with all Fosta regimens demonstrating inferior DAS28-CRP responses compared to ADA at week 24. However, the performance of ADA monotherapy in this trial was at the upper end of that observed in previous studies. Fosta is being evaluated in combination with DMARDs in the ongoing Phase III programme. Acknowledgements: Study funded by AstraZeneca. Disclosure of Interest: P. Taylor Grant/research support from: UCB, Consultant for: AstraZeneca, Pfizer, Lilly and Celgene, M. Genovese Grant/research support from: AstraZeneca, Consultant for: AstraZeneca, M. Greenwood Shareholder of: AstraZeneca, Employee of: AstraZeneca, M. Ho Employee of: AstraZeneca, E. Nasonov Grant/research support from: Servier, Speakers bureau: Roche, Schering-Plough Corporation and MSD, B. Oemar Employee of: AstraZeneca, R. Stoilov: None Declared, J. Vencovsky: None Declared, M. Weinblatt Consultant for: AstraZeneca and AbbVie (formerly Abbott)